Structural evolution of carbon from methane pyrolysis in microwave plasma - Arman Miniyazov; Mazhyn Skakov; Timur Tulenbergenov; Igor Sokolov; Nuria Mukhamedova; Alina Agatanova; Aisara Sabyrtaeva; Tolkyn Akhmedi (Carbon Trends)
This research investigates the synthesis of carbon materials produced via methane pyrolysis using microwave plasma at different magnetron powers (0.6, 1.0, and 1.4 kW), aiming to analyze how the power levels affect the properties of the resulting materials. Various analytical techniques were implemented to characterize these materials. The microstructure was examined using scanning electron microscopy (SEM), phase composition through X-ray diffraction (XRD), and surface area along with porosity using low-temperature nitrogen adsorption methods (BET and BJH). Findings indicate that increasing magnetron power reduces the agglomerate size and enhances structural ordering in carbon layers, progressing from amorphous to turbostratic and ultimately to graphite-like structures. Plasma pyrolysis of methane conducted at 0.6 kW yields carbon materials with notably high adsorption characteristics.